Employer preferences and political alignments during the Eurocrisis: Evidence from the Portuguese case - Lisi, M.; Loureiro, J. (Business and Politics, 2019)
This paper strives to shed light on the interaction between business groups and the main governing parties after the onset of the economic crisis through a thick narrative approach. By focusing on the Portuguese case, the study aims to examine the preferences of the employer confederations during the distinct phases of the economic crisis and to analyze the political alignments established with different party governments. This contribution confirms the fragmentation of business interests on the one hand and tensions between the right-wing government and the main employer confederations on the other. While a pragmatic approach to party politics seems to be the predominant trend, historical and institutional legacies are still important factors when considering the actions and inner tensions of these organizations.